Digital Government Strategy, Government Models and Technology - Wirtz, Bernd W. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Digitization, the global networking of individuals and organizations, and the transition from an industrial to an information society are key reasons for the importance of digital government. In particular, the enormous influence of the Internet as a global networking and communication system affects the performance of public services. This textbook introduces the concept of digital government as well as digital management and provides helpful insights and strategic advice for the successful implementation and maintenance of digital government systems.
Part I: Concept and Strategy of Digital Government -- 1. Introduction -- 2. The Information Society and Digital Government -- 3. The Concept and Strategy of Digital Government -- 4. Digital Transformation and Digital Organization -- Part II: Technology, Smart City and Digital Government Models -- 5. Digital Government Technology -- 6. Artificial Intelligence, Big Data, Cloud Computing, and Internet of Things -- 7. Social Media and Public Disinformation -- 8. Smart City -- 9. Digital Government Business Models -- Part III: Digital Government Services, Channels and Implementation -- 10. User-Driven Digital Government -- 11. Digital Government Services -- 12. Multichannel E-Service Delivery -- 13. Success Factors of Digital Government -- 14. Digital Government Implementation -- Part IV: Digital Government Cases and Outlook -- 15. Digital Government Case Studies -- 16. Digital Government Outlook.
Keywords: Business information services; Public administration; Nonprofit organizations; IT in Business; Public Administration; Non-Profit Organizations and Public Enterprises